Acorns as a food resource - Pacheco, R. (2021)
The oaks (Quercus spp.) comprise the largest genus Fagaceae, an important family of evergreen or deciduous trees of temperate and tropical climatic areas. The acorn is a one-seeded nut, the hard, dry and indehiscent fruit of oaks, derived from a unilocular ovary of fused carpels. Acorns are an interesting source of carbohydrates, fats and fibers and also contain protein, amino acids and vitamins, mostly A and C. Additionally, it has been proven its antioxidant effects. Appreciation of acorn has been increasing, because of its potential as a food resource. The goal of the present review is to compile the published information about nutritional, phytochemical and bioactive composition of acorns.